2022
DOI: 10.1038/s41598-022-05749-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological characteristics associated with the presence of the IS6110 Mycobacterim tuberculosis transposon in neoplastic cells from non-small cell lung cancer patients

Abstract: Lung cancer (LC) and pulmonary tuberculosis (TB) are the deadliest neoplastic and bacterial infectious diseases worldwide, respectively. Clinicians and pathologists have long discussed the co-existence of LC and TB, and several epidemiologic studies have presented evidence indicating that TB could be associated with the development of LC, particularly adenocarcinoma. Nonetheless, this data remains controversial, and the mechanism which could underlie the association remains largely unexplored. Some bioinformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(57 reference statements)
0
6
0
1
Order By: Relevance
“…The direct work in cancer samples as outlined above [1,2,3,5,10,11,12,13] has indicated the potential linkage of LGT in cancer, and studies could be expanded to cover larger datasets and include longitudinal tracking of larger patient cohorts. While most LGT insertions should be neutral in impact, large scale studies using healthy and non-healthy donors would indicate if there were hot spots on the genome that cause cancer, if these hotspots changed over time, and if these areas were linked to ancestral genes as suggested by the proponents of the serial atavism model [21].…”
Section: Hypothesis Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct work in cancer samples as outlined above [1,2,3,5,10,11,12,13] has indicated the potential linkage of LGT in cancer, and studies could be expanded to cover larger datasets and include longitudinal tracking of larger patient cohorts. While most LGT insertions should be neutral in impact, large scale studies using healthy and non-healthy donors would indicate if there were hot spots on the genome that cause cancer, if these hotspots changed over time, and if these areas were linked to ancestral genes as suggested by the proponents of the serial atavism model [21].…”
Section: Hypothesis Testingmentioning
confidence: 99%
“…PBTS2, Micrococcus luteus strain trpE16 and M. luteus NCTC 2665 integrated into the genome of an eosinophilic leukaemia patient [11]. Arrieta et al (2022) evaluated the presence of the IS6110 Mycobacterim tuberculosis (Mtb) transposon on the primary tumour DNA of eighty-eight patients through end-point PCR, with results showing that 40.9% (36/88) had a positive endpoint PCR for the IS6110 transposon [12]. Shotgun sequencing from two samples identified traces of MTb genomes present in lung adenocarcinomas tumour tissue, suggesting that similar Mtb strains could be infecting both patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). In addition, a retrospective cohort study performed in Latin American displayed MTB DNA sequence IS6110 identified in the nuclear area of tumor cells in the lung [ 55 ]. These findings provide several evidences for a causal link between lung cancer and mycobacterium secreted protein and its DNA.…”
Section: Effector Protein Of Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…Despite the current efforts to establish screening programs for high-risk individuals in several countries [ 30 , 31 , 32 ], the majority of patients worldwide are diagnosed with advanced disease, when surgery is mostly no longer feasible [ 28 , 33 , 34 ]. In addition, advances in systemic therapy such as novel targeted agents and immunotherapy, and improved techniques in radiotherapy, are still mostly circumscribed to patients with socioeconomic privileges, and as such most patients with lung cancer worldwide lack access to these advances [ 33 ]. This underscores the urgent necessity to identify new therapeutic approaches to overcome resistance mechanisms and which are available and accessible to the more than 2 million people diagnosed with lung cancer every year [ 35 , 36 ].…”
Section: Overview Of Lung Cancer: Epidemiology Treatment and Challengesmentioning
confidence: 99%